Cutting force analysis to estimate the friction force in linear guideways of CNC machine. (May 2016) - Sparham, Mahdi; Sarhan, Ahmed A.D.; Mardi, N.A.; Dahari, M.; Hamdi, M.
Highlights: Guideways are significant parts in CNC machines to yield precision and accuracy. Friction in guideways is a major factor that prevents more accuracy and precision. The friction forces are modeled using the analyzed cutting forces on guideways. Coefficient of frictions are measured experimentally at dry lubrication condition. The friction force is estimated using the identified coefficient of friction. Abstract: Linear guideways are widely applied in advanced machinery industries worldwide for different types of CNC machine (e.g., turning, milling, grinding, and gantry). All of these machines require accuracy and precision in the machining operations to manufacture quality products. The cutting operation in product manufacturing occurs with the displacement of machine tables on linear guideways. For this reason, linear guideways are significant parts and have sensitive locations in CNC machines to yield precision and accuracy. Friction is a major factor of deformation in guideways and non-smooth motion that prevents superior accuracy and precision in machine operations. Moreover, the frictional behavior in linear guideways is one of the most crucial challenges for CNC machining, such that between two parts of friction and temperature stimulus there will be stick-slip motion, wear and corrosion of the parts. Thus, manufacturers are interested in these machines, particularly to facilitate this process with an actual lubrication system. Hence, friction force estimation and modeling in CNC machine guideways is used to overcome these problems by controlling the lubrication operation. In this research work, the cutting force components including, longitudinal force ( FL ), radial force ( Fr ) and tangential force ( Ft ) are measured during cutting process. These cutting force values are corresponding to different cutting conditions includes, spindle speed, depth of cut, and feed rate. The cutting force components and the weight of the moving parts are analyzed and transferred to the CNC machine guideways. The friction force on linear guideways of machine tools is modeled based on the analyzed and transferred force components on the guideways during cutting. The static and kinetic coefficient of friction are measured experimentally in dry lubrication condition hence the friction force components can be obtained. The friction force are estimated using the identified coefficient of friction.